Evaluation of the Operational Environment Factors of Nature Conservation Policy Implementation: Cases of Selected EU and Non-EU Countries - Pezdevšek Malovrh, Špela; Paletto, Alessandro; Posavec, Stjepan; Dobšinská , Zuzana; Đorđević, Ilija; Marić, Bruno; Avdibegović, Mersudin; Kitchoukov, Emil; Stijović, Aleksandar; Trajkov, Pande; Laktić, Tomislav (MDPI AG, 2019)
The complex policy decision-making situation around nature conservation requires examination of the operational environment. This study develops and tests a three-phase analytical framework for the evaluation of operational environment factors influencing nature conservation policy implementation. The four important operational environment factors (legal, policy, economic, and social) have been identified, to build up a framework. The framework was tested in selected countries and includes experts’ opinions. Experts (n = 44) from five EU countries (Bulgaria, Croatia, Italy, Slovakia, and Slovenia) and four non-EU countries (Bosnia and Herzegovina, North Macedonia, Montenegro, and Serbia) defined and evaluated the factors and sub-factors that affect the operational environment related to nature conservation policy implementation. The results show policy changes arising from the new governance requirements introduced by changed political regime and Europeanization are key driving factors for changes in the nature conservation operational environment. For nature conservation, these wide-reaching changes have led to new political and legal frameworks, new institutional set-ups and multilevel governance frameworks, new establishment of protected areas and Natura 2000 network, and the re-allocation of financial resources and inclusion of non-state actors in policy decision-making. However, there are also some challenges and unsolved problems that need further attention from policy decision-makers and institutions, especially related to the institutional gap, sustainable financing of nature conservation, transposition of the EU Directives into legal systems, designation of sites or improving their implementation, implementation of innovative funding schemes, and a transparent participatory process. This analytical framework can be applied to various problems related to any environmental issues or other policy implementation or management, and other sectors where public decision-making is combined with stakeholders’ engagement.
Keywords: biodiversity conservation; nature conservation policy; operational environment; legal; policy; economic and social factors; evaluation framework; protected areas; Natura 2000 network